Analisis Pengaruh Bauran Pemasaran (7P) Terhadap Keputusan Pembelian Produk Non Resep dan Loyalitas Pelanggan Apotek 24 Jam di Kota Administrasi Jakarta Utara - Utami, Santi Yanuarti; Prasetiyo, Andri; Ahmar, Nurmala (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
During the implementation of National Health Insurance (JKN), 24-hour pharmacies without a doctor's practice in North Jakarta Administrative City face a number of significant problems that affect their operations and sustainability. Currently, the development of pharmacies is increasing. This has led to business competition between pharmacies, especially 24-hour pharmacies without a doctor's practice and fluctuations in terms of visits and sales. This study seeks to investigate the effect along with results by interviews related to The marketing elements (7P), non-prescription product buying behavior and customer retention of 24-hour pharmacies on North Jakarta Administrative City. This investigation adopts a descriptive-analytical approach. The research method is a mix methods explanatory sequential method, namely this study is quantitative and continued with qualitative. Product, price, persons, procedure and tangible evidence make a substantial difference to the choice to purchase non-prescription products and customer loyalty of 24-hour pharmacies in North Jakarta City Administration, while place and promotion do not exert a considerable effect on the buying choice non-prescription goods and customer loyalty of 24-hour pharmacies in North Jakarta City Administration. Product is seen from the side of being safe, useful, in a state of intact and good physical form or condition, complete, varied and always available or never empty. Price is viewed from the perspective of being in accordance with quality, benefits and cheaper than other pharmacies. Place is analyzed from the angle of distance, easy to find and easy to access. Promotion is observed from the standpoint of recommendations, discounts or prizes or draws and the use associated with social networking platforms. People serve as seen from this side by having broad and good knowledge, being friendly, always ready and fast to serve customers. Process is seen from the side of providing clear information, providing health education outside of the required treatment, waiting time for taking medicine right according to the queue, fast and easy to get medicine after 10 pm. Physical evidence is seen from the neat layout, comfortable pharmacy waiting room, spacious vehicle parking area. Purchasing decisions are seen from the purchasing side according to what is needed, searching for information first, comparing prices with other pharmacies, purchasing according to ability and purchasing because it is useful. Customer loyalty is seen from the side of returning and making purchases because they are satisfied, will not switch to another pharmacy and continue to make purchases, recommending the pharmacy, defending and supporting the pharmacy when facing criticism or competition.